Pengaruh Suasana Toko, Kualitas Pelayanan Dan Kualitas Produk Terhadap Kepuasan Pelanggan Di Ramayana Mall Dinoyo (Studi Kasus Pada Mahasiswa FEB UNISMA) - Lutfi Zainul Hasan; Nur Hidayati; Aleria Irma Hatneny (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this study was to determine the effect of store atmosphere, service quality and product quality on customer satisfaction at Ramayana Mall Dinoyo, and to see how much customer satisfaction, especially for FEB UNISMA students who visited Ramayana Mall Dinoyo, as many as 90 respondents as a sample using the Maholtra formula. . The method in this study uses an Explanatory Research approach. With the results of the F test analysis test, it shows that the X variable (store atmosphere, service quality and product quality) simultaneously has a significant positive effect on the Y variable (customer satisfaction) at Ramayana Mall Dinoyo and the results of the t test analysis show that the X variable (store atmosphere, service quality and product quality) partially have a significant positive effect on the Y variable (customer satisfaction) at Ramayana Mall Dinoyo. Keyword : Store Atmosphere, Product Quality, Service Quality, Costumer Satisfaction